Green Web or megabiased clock? Plant fossils from Gondwanan Patagonia speak on evolutionary radiations - Wilf, Peter (2015)
Evolutionary divergence-age estimates derived from molecular ‘clocks’ are frequently correlated with paleogeographic, paleoclimatic and extinction events. One prominent hypothesis based on molecular data states that the dominant pattern of Southern Hemisphere biogeography is post-Gondwanan clade origins and subsequent dispersal across the oceans in a metaphoric ‘Green Web’. We tested this idea against well-dated Patagonian fossils of 19 plant lineages, representing organisms that actually lived on Gondwana. Most of these occurrences are substantially older than their respective, often post-Gondwanan molecular dates. The Green Web interpretation probably results from directional bias in molecular results. Gondwanan history remains fundamental to understanding Southern Hemisphere plant radiations, and we urge significantly greater caution when using molecular dating to interpret the biological impacts of geological events.